INTER-RELIGIOUS DIALOGUE IN BANGLADESH - Hacha, Simon (Journal of Dharma, 2000)
The present Bangladesh was called East Bengal culturally united with West Bengal in the undivided India. In 1947 when Pakistan was created on the basis of religion, the majority of the people of East Bengal being Muslims, belonged to Pakistan and was known as East Pakistan. Bangladesh as an independent country came into existence after the war of liberation against Pakistan -in 1971 in spite of the fact that in both West and East Pakistan the majority were Muslims.